Chitinase‐3‐like protein 1 ameliorates atherosclerotic responses via PPARδ‐mediated suppression of inflammation and ER stress. Issue 8 (8th May 2018) - Jung, Tae Woo; Park, Hyung Sub; Choi, Geum Hee; Kim, Daehwan; Jeong, Ji Hoon; Lee, Taeseung
Abstract: Chitinase 3‐like protein 1 (CHI3L1) is a novel biomarker of systemic inflammation. However, the effects of CHI3L1 on the progression of atherosclerosis remain to be explored. In the current study, we found that CHI3L1 induces peroxisome proliferator‐activated receptor delta (PPARδ) expression, leading to a dose‐dependent increase in oxygen‐regulated protein 150 (ORP150) expression. We demonstrated that CHI3L1 suppresses atherosclerotic reactions caused by LPS treatment via a PPARδ‐dependent pathway. Treatment of HUVECs and THP‐1 cells with CHI3L1 suppressed LPS‐induced phosphorylation of nuclear factor kappa B (NFκB) and secretion of proinflammatory cytokines such as TNFα and MCP‐1. In HUVECs, expression of adhesion molecules and LPS‐stimulated adhesion of THP‐1 cells to the endothelium were significantly reduced after CHI3L1 treatment. Furthermore, LPS‐induced endoplasmic reticulum (ER) stress and cell apoptosis were significantly ameliorated after treatment of HUVECs with CHI3L1. Particularly, all of the pro‐atherosclerotic effects were significantly mitigated by treatment with small interfering (si) RNA for PPARδ. In conclusion, CHI3L1 ameliorates LPS‐induced atherosclerotic reactions via PPARδ‐mediated suppression of inflammation and ER stress. Abstract : Chitinase‐3‐like protein 1 (CHI3L1) attenuates LPS‐induced inflammation through PPARδ‐dependent signaling. CHI3L1 induces ORP150 expression and suppression of ER stress through PPARδ‐mediated pathway. CHI3L1 attenuates atherosclerotic responses through PPARδ‐mediated suppression of inflammation and ER stress.